2011
DOI: 10.1136/bmjqs.2010.050880
|View full text |Cite
|
Sign up to set email alerts
|

Identifying continuous quality improvement publications: what makes an improvement intervention 'CQI'?

Abstract: BackgroundThe term continuous quality improvement (CQI) is often used to refer to a method for improving care, but no consensus statement exists on the definition of CQI. Evidence reviews are critical for advancing science, and depend on reliable definitions for article selection.MethodsAs a preliminary step towards improving CQI evidence reviews, this study aimed to use expert panel methods to identify key CQI definitional features and develop and test a screening instrument for reliably identifying articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…This is in line with prevailing definitions of climate as ‘the policies, practices, and procedures as well as the behaviours that get rewarded, supported, and expected in a work setting’ [85]. It is also consistent with recent attempts to identify an operational definition for CQI interventions, which focused on CQI methods such as the use of data to design changes [86]. …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with prevailing definitions of climate as ‘the policies, practices, and procedures as well as the behaviours that get rewarded, supported, and expected in a work setting’ [85]. It is also consistent with recent attempts to identify an operational definition for CQI interventions, which focused on CQI methods such as the use of data to design changes [86]. …”
Section: Resultssupporting
confidence: 82%
“…First, there is limited consensus in the literature on what defines a CQI intervention and its components, and large variability in the content of CQI interventions across studies [86]. In part, this is attributed to the evolution and local adaptation of CQI interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous quality improvement procedures are a distinctive component of QA systems intended to maximize the utility of implementation evaluation in routine practice via site-specific performance feedback (O'Neill et al 2011). …”
Section: Need For Efficient Fidelity Measures To Support Ebi Quality mentioning
confidence: 99%
“…We showed that, while these features can be reliably abstracted from the literature, there are few articles that include all of them [19]. We also found that articles are so diverse in terms of where they report the features (e.g.…”
Section: Discussionmentioning
confidence: 99%